Terrorism Prevention: A General Model - Franz Dietrich
In this paper, I present and discuss a method for modelling an important trade-off faced by terrorism prevention policies: the trade-off between, on the one hand, trying to reduce people's inclination towards terrorism, and, on the other hand, trying to protect society against existing terrorists. In general, cause-related policies reduce inclination towards terrorism (first goal), involving measures such as raising the standard of living, and symptom-related policies reduce the power of terrorists (second goal), involving measures such as capturing and detaining terrorists. But, crucially, symptom-related policies also affect the inclination towards terrorism, through (desirable) deterrence and (undesirable) 'hate effects'. If 'hate effects' dominate over deterrence, more toughness overall increases inclination, possibly overcompensating the 'capture success'. So, symptom-related policies may face a trade-off between capturing terrorists, and thereby possibly creating new terrorists. Through the modelling method presented, both policy goals are simultaneously taken into account.terrorism, threat, war, symptom-related policy, cause-related policy, development policy, development aid, deterrence, hate effect, trade-off, game theory